Interkinase domain of kit contains the binding site for phosphatidylinositol 3' kinase. - Lev, S (1992)
Our previous analysis of the signal transduction pathway used by the c-kit-encoded receptor for the stem cell factor (SCF) indicated efficient coupling to the type I phosphatidylinositol 3' kinase (PI3K). In an attempt to localize the receptor's site of interaction with PI3K, we separately deleted either the noncatalytic 68-amino-acid-long interkinase domain or the carboxyl-terminal portion distal to the catalytic sequences. Loss of ligand-induced association of PI3K with the former deletion mutant and retention of the PI3K association by the carboxyl-terminally deleted receptor implied interactions of PI3K with the kinase insert. This was further supported by partial inhibition of the association by an anti-peptide antibody directed against the kinase insert and lack of effect of an antibody directed to the carboxyl tail of the SCF receptor. A bacterially expressed kinase insert domain was used as a fusion protein to directly test its presumed function as a PI3K association site. This protein bound PI3K from cell lysate as demonstrated by PI3K activity and by an associated phosphoprotein of 85 kDa. The association was dependent on phosphorylation of the tyrosine residues on the expressed kinase insert. On the basis of these observations, we conclude that the kinase insert domain of the SCF receptor selectively interacts with the p85 regulatory subunit of PI3K and that this association requires phosphorylation of tyrosine residues in the kinase insert region, with apparently no involvement of the bulk cytoplasmic structure or tyrosine kinase function of the receptor.